2016
DOI: 10.1002/jmv.24712
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus infection in southwestern Saudi Arabia: Are we still in the plateau phase?

Abstract: The aim was to study the seroprevalence of Hepatitis C virus (HCV) infection and related risk factors in Aseer region in southwestern Saudi Arabia, the region known to be of the highest endemicity of viral hepatitis. In a cross-sectional study, all participants were interviewed using structured questionnaire. HCV infection was diagnosed using fourth-generation ELISA. All positive and equivocal HCV serology results were further confirmed by using a qualitative confirmatory RT-PCR. The study enrolled 10,234 part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…The present study revealed a prevalence rate of HCV infection among non-diabetic patients of 2.0%. This figure is comparable to the estimated prevalence rate among general population in Southwestern Saudi Arabia of 2.2% (95% CI: 1.9–2.5%) [ 20 ].…”
Section: Discussionsupporting
confidence: 77%
“…The present study revealed a prevalence rate of HCV infection among non-diabetic patients of 2.0%. This figure is comparable to the estimated prevalence rate among general population in Southwestern Saudi Arabia of 2.2% (95% CI: 1.9–2.5%) [ 20 ].…”
Section: Discussionsupporting
confidence: 77%
“…Rates of seropositivity for HCV vary between countries and different regions in the same country. The Aseer region in southwestern Saudi Arabia had an anti-HCV prevalence rate of 2.2% [ 24 ], while Alexandria, Egypt, had a high prevalence rate of 23.2% [ 25 ]. In contrast, the prevalence of anti-HCV rate decreased in voluntary donors in Cairo from 4.2 to 1.5% [ 18 ].…”
Section: Discussionmentioning
confidence: 99%